Method for preparing ultra-stable metallic glass
By smelting and heat treatment of alloy ingredients, ultra-steady state metal glass is prepared, which solves the problems of complex and low production efficiency of the preparation of ultra-steady state metal glass in the prior art, realizes an efficient and economical preparation process, and improves the performance and applicability of the material.
Patent Information
- Application Number
- CN202411637322.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-15
- Publication Date
- 2025-03-28
- Estimated Expiration
- 2044-11-15
AI Technical Summary
The prior art has problems such as complex methods, low production efficiency, high cost and limited size when preparing ultra-steady metal glass, which is difficult to meet practical application needs.
Cast metal glass is prepared by smelting the alloy ingredients and undergoing glass-glass transformation without crystallization by heat treatment, and finally, supersteady metal glass is prepared. The process parameters of the heat treatment are determined by differential scanning calorimetry curves to ensure that the glass-glass transition and the temperature at which no crystallization occurs is the final temperature of the heat treatment.
The simplification of the preparation method, the improvement of production efficiency, the reduction of cost, and the unsize limit of ultra-steady metal glass, high anti-aging, high anti-crystallization ability, better mechanical properties and durability, are achieved, and are suitable for different application scenarios.
Smart Images

Figure BDA0005137436410000131 
Figure HDA0005137436420000011 
Figure HDA0005137436420000012
Abstract
Description
Technical Field
[0001] The invention relates to the field of amorphous alloys, and in particular to a method for preparing ultrastable metallic glass. Background Art
[0002] In the field of amorphous alloys, the traditional method for preparing ultra-stable metallic glass mainly includes physical vapor deposition (PVD). This method can prepare ultra-stable metallic glass films by adjusting the temperature of the deposition substrate (around 0.8Tg) and the deposition rate. In addition, natural aging is also a method for preparing ultra-stable metallic glass, which relies on the natural relaxation process of metallic glass over time to achieve a more stable structural state. However, the natural aging process is very slow and usually takes years or even decades.
[0003] Although the PVD method can prepare ultra-stable glass on a laboratory time scale, it has some obvious limitations. First, the PVD method is mainly suitable for the preparation of thin film materials, and usually can only prepare two-dimensional films with a thickness of tens to hundreds of nanometers, which limits its application in three-dimensional structures. Secondly, the films prepared by the PVD method often have strong anisotropy, which may affect the comprehensive performance of the material. In addition, the natural aging method has almost no practical application value due to its extremely long time span.
[0004] Therefore, it is necessary to develop a new method for preparing ultrastable metallic glass with simple preparation method, high production efficiency, low cost and no size restriction. Summary of the invention
[0005] The present invention aims to solve at least one of the technical problems existing in the prior art to a certain extent. To this end, the present invention provides a method for preparing ultra-stable metallic glass. The preparation method of the present invention has the advantages of simple preparation method, high production efficiency, low cost, no size restriction, and wide applicability to alloy systems with glass-glass transition characteristics. The ultra-stable metallic glass prepared according to the present invention has no size restriction, high aging resistance, high crystallization resistance, better mechanical properties and durability, and is suitable for different application scenarios.
[0006] In the first aspect of the present invention, a method for preparing ultra-stable metallic glass is proposed. According to an embodiment of the present invention, it includes: S1: melting alloy ingredients to obtain cast metallic glass; S2: heat treating the cast metallic glass to make it undergo glass-glass transition without crystallization, so as to obtain ultra-stable metallic glass; wherein, the process parameters of the heat treatment are determined by the differential scanning calorimetry curve of the cast metallic glass, and the temperature at which the glass-glass transition without crystallization occurs is determined by the exothermic peak in the differential scanning calorimetry curve as the final temperature of the heat treatment. The inventor first prepares ordinary metallic glass by alloy melting and rapid cooling treatment, then heats the ordinary metallic glass to make it undergo glass-glass transition without crystallization, and then cools it to room temperature, thereby preparing ultra-stable metallic glass. The preparation method of the present invention has the advantages of simple preparation method, high production efficiency, low cost, no size restriction, and wide applicability to alloy systems with glass-glass transition characteristics. The ultrastable metallic glass prepared according to the present invention has high aging resistance, high crystallization resistance, better mechanical properties and durability, and can be suitable for different application scenarios.
[0007] According to an embodiment of the present invention, the method for preparing ultrastable metallic glass may also have the following additional technical features:
[0008] According to an embodiment of the present invention, the alloy ingredients include two or more of titanium, zirconium, hafnium, copper, nickel, beryllium, cobalt, aluminum, niobium, lanthanum, cerium and cobalt.
[0009] According to an embodiment of the present invention, the alloy ingredients include titanium, zirconium, copper, nickel and beryllium. Therefore, the preparation method of the present invention is applicable to an alloy system including titanium, zirconium, copper, nickel and beryllium alloy ingredients and having glass-glass transition characteristics.
[0010] According to an embodiment of the present invention, the alloy ingredients include titanium, hafnium, copper, nickel and beryllium.
[0011] According to an embodiment of the present invention, the alloy ingredients include titanium, zirconium, hafnium, copper, nickel and beryllium.
[0012] According to an embodiment of the present invention, the smelting process comprises the following steps: a. arc melting the alloy ingredients to obtain the master alloy ingot; b. melting the master alloy ingot by induction melting, and then cooling and solidifying it to obtain the cast metallic glass.
[0013] According to an embodiment of the present invention, the heat treatment further comprises: heating the cast metallic glass to a temperature at which a glass-glass transition occurs but crystallization does not occur, and performing a cooling treatment to obtain an ultra-stable metallic glass.
[0014] According to an embodiment of the present invention, the heat treatment further includes: heating the cast metallic glass to a preset temperature at which glass-glass transition occurs and crystallization does not occur and performing a heat preservation treatment, and performing a cooling treatment after the heat preservation treatment to obtain an ultra-stable metallic glass; wherein the preset temperature is lower than the final temperature of the heat treatment.
[0015] In a second aspect of the present invention, the present invention provides an ultra-stable metallic glass. According to an embodiment of the present invention, the ultra-stable metallic glass is prepared according to the aforementioned method. The ultra-stable metallic glass of the present invention has no size restriction, high aging resistance, high anti-crystallization ability, better mechanical properties and durability, and is suitable for different application scenarios.
[0016] According to an embodiment of the present invention, the above-mentioned ultrastable metallic glass may also have the following additional technical features:
[0017] According to an embodiment of the present invention, the alloy composition of the ultrastable metallic glass is expressed as Ti in atomic percentage. a Zr b Cu c Ni d Be e , among which: 19%≤a≤21%, 19%≤b≤21%, 19%≤c≤21%, 19%≤d≤21%, 16%≤e≤24%, a+b+c+d+e=100%.
[0018] According to an embodiment of the present invention, the alloy composition of the ultrastable metallic glass is expressed as Ti in atomic percentage. A Hf B Cu C Ni D Be E , among which: 19%≤A≤21%, 19%≤B≤21%, 19%≤C≤21%, 19%≤D≤21%, 16%≤E≤24%, A+B+C+D+E=100%.
[0019] According to an embodiment of the present invention, the alloy composition of the ultrastable metallic glass is expressed as Ti in atomic percentage. I Zr II Hf III Cu IV Ni V Be VI , where: I=II=III, 12%≤I≤14%, IV=V=VI, 19%≤IV≤22%, I+II+III+IV+V+VI=100%.
[0020] The preparation method of the present invention has the advantages of simple preparation method, high production efficiency, low cost, no size restriction, and wide applicability to alloy systems with glass-glass transition characteristics. The ultrastable metallic glass prepared according to the present invention has no size restriction, high aging resistance, high crystallization resistance, better mechanical properties and durability, and is suitable for different application scenarios. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] The above and / or additional aspects and advantages of the present invention will become apparent and easily understood from the description of the embodiments in conjunction with the following drawings, in which:
[0022] Figure 1 The differential scanning calorimetry curves of the cast metallic glass I and the ultrastable metallic glass I in Example 1 of the present invention are shown in FIG. 1 , wherein the heating rate is 10 K min -1 ;
[0023] Figure 2 The differential scanning calorimetry curves of the cast metallic glass II and the ultrastable metallic glass II in Example 2 of the present invention are shown in FIG. 1 , wherein the heating rate is 10 K min -1 ;
[0024] Figure 3 The differential scanning calorimetry curves of the cast metallic glass III and the ultrastable metallic glass III in Example 3 of the present invention are shown in FIG. 1 , wherein the heating rate is 10 K min -1 ;
[0025] Figure 4 The differential scanning calorimetry curves of the cast metallic glass IV and the ultrastable metallic glass IV in Example 4 of the present invention are shown in FIG. 1 , wherein the heating rate is 10 K min -1 ;
[0026] Figure 5 The differential scanning calorimetry curves of the cast metallic glass V and the ultrastable metallic glass V in Example 5 of the present invention are shown in FIG. 1 , wherein the heating rate is 10 K min -1 ;
[0027] Figure 6 XRD results of cast metallic glass I and ultrastable metallic glass I in Example 6 of the present invention;
[0028] Figure 7 XRD results of cast metallic glass II and ultrastable metallic glass II in Example 6 of the present invention;
[0029] Figure 8 XRD results of cast metallic glass III and ultrastable metallic glass III in Example 6 of the present invention;
[0030] Fig. 9XRD results of cast metallic glass IV and ultrastable metallic glass IV in Example 6 of the present invention;
[0031] Fig.10 XRD results of cast metallic glass V and ultrastable metallic glass V in Example 6 of the present invention;
[0032] Fig.11 TEM results of cast metallic glass I and ultrastable metallic glass I in Example 6 of the present invention, wherein (a) is a high-resolution transmission electron micrograph and a selected area electron diffraction pattern of cast metallic glass I, (b) is a high-angle annular dark field image of cast metallic glass I, (c) is a high-resolution transmission electron micrograph and a selected area electron diffraction pattern of ultrastable metallic glass I, and (d) is a high-angle annular dark field image of ultrastable metallic glass I;
[0033] Fig.12 is the pair distribution function G(r) curve of the cast metallic glass I and the ultrastable metallic glass I in Example 6 of the present invention;
[0034] Fig.13 Flash DSC results of cast metallic glass I and ultrastable metallic glass I in Example 6 of the present invention, with a heating rate of 1000K s -1 ;
[0035] Fig.14 The comparative density test results of cast metallic glass I and ultrastable metallic glass I in Example 6 of the present invention;
[0036] Fig.15 The ultrastable metallic glass I in Example 6 of the present invention is g XRD patterns, DSC curves and nanoindentation load-displacement curves before and after annealing at +70K for 10h, where (a) is the superstable metallic glass I at its T g XRD patterns of the ultrastable metallic glass I before and after annealing at +70K for 10h. (b) g DSC curves of the superstable metallic glass I before and after annealing at +70K for 10h. (c) g Nanoindentation load-displacement curves before and after annealing at +70K for 10h. DETAILED DESCRIPTION
[0037] The embodiments of the present invention are described in detail below. The embodiments described below are exemplary and are only used to explain the present invention, and should not be understood as limiting the present invention.
[0038] The endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.
[0039] In this document, the terms “include” or “comprising” are open expressions, that is, including the contents specified in the present invention but not excluding other contents.
[0040] As used herein, the terms "optionally", "optional" or "optionally" generally mean that the subsequently described event or circumstance may but need not occur, and that the description includes instances where the event or circumstance occurs and instances where it does not.
[0041] Terms and Definitions
[0042] In this article, the term "glass-to-glass transition" refers to the transition from one glass to another, during which the structure, properties, and energy state of the glass change, usually accompanied by heat release (an exothermic peak occurs when the temperature rises). In the present invention, after undergoing the glass-to-glass transition, the original cast metallic glass is transformed into an ultrastable metallic glass.
[0043] In this article, the term "final temperature" refers to the highest temperature reached by a sample during a heating test or experiment, and in the present invention, it specifically refers to the temperature at which the cast metallic glass is heated to completely complete the glass-glass transition and no crystallization occurs.
[0044] In this article, the term "ultrastable metallic glass" is an amorphous metal material with high thermodynamic and kinetic stability. Compared with traditional metallic glass, it has a more stable amorphous structure, higher thermal stability, better anti-aging properties, better anti-crystallization ability, better mechanical properties and durability.
[0045] In this article, the term "master alloy ingot" refers to an alloy material that contains the alloy components and ingredients, is completely melted into an alloy melt and then cooled and solidified. The composition is very uniform and has been repeatedly smelted and processed to ensure that its chemical composition and physical properties meet specific standards.
[0046] In this article, the term "complete crystallization" refers to the process of a material transforming from an amorphous state or a partially crystalline state to a completely ordered crystalline state; in amorphous material metallic glass, complete crystallization usually involves the transformation of atoms from a long-range disordered arrangement to a regular, periodic arrangement, and the temperature range in which complete crystallization occurs can be determined by the crystallization starting point and ending point corresponding to the crystallization exothermic peak of the differential scanning calorimetry curve.
[0047] Method for preparing ultrastable metallic glass
[0048] The present invention proposes a method for preparing ultra-stable metallic glass. According to an embodiment of the present invention, the method comprises: S1: melting alloy ingredients to obtain cast metallic glass; S2: heat treating the cast metallic glass to make it undergo glass-glass transition and not crystallize, so as to obtain ultra-stable metallic glass; wherein the process parameters of the heat treatment are determined by the differential scanning calorimetry curve of the cast metallic glass, wherein the temperature of the glass-glass transition and not crystallize determined by the exothermic peak in the differential scanning calorimetry curve is used as the end temperature of the heat treatment. The inventor first prepares ordinary metallic glass by alloy melting and rapid cooling treatment, then heats the ordinary metallic glass to make it undergo glass-glass transition and not crystallize, and then cools it to room temperature, thereby preparing ultra-stable metallic glass. The preparation method of the present invention has the advantages of simple preparation method, high production efficiency, low cost, no size restriction, and wide applicability to alloy systems with glass-glass transition characteristics. The ultra-stable metallic glass prepared according to the present invention has high anti-aging, high anti-crystallization ability, better mechanical properties and durability, and is suitable for different application scenarios.
[0049] According to an embodiment of the present invention, the alloy ingredients include two or more of titanium, zirconium, hafnium, copper, nickel, beryllium, cobalt, aluminum, niobium, lanthanum, cerium and cobalt. Therefore, the preparation method of the present invention is widely applicable to alloy systems with glass-glass transition characteristics.
[0050] According to an embodiment of the present invention, the alloy ingredients include titanium, zirconium, copper, nickel and beryllium. Therefore, the preparation method of the present invention is applicable to an alloy system including titanium, zirconium, copper, nickel and beryllium alloy ingredients and having glass-glass transition characteristics.
[0051] According to an embodiment of the present invention, the alloy ingredients include titanium, hafnium, copper, nickel and beryllium. Therefore, the preparation method of the present invention is applicable to an alloy system including titanium, hafnium, copper, nickel and beryllium alloy ingredients and having glass-glass transition characteristics.
[0052] According to an embodiment of the present invention, the alloy ingredients include titanium, zirconium, hafnium, copper, nickel and beryllium. Therefore, the preparation method of the present invention is applicable to an alloy system including titanium, zirconium, hafnium, copper, nickel and beryllium alloy ingredients and having glass-glass transition characteristics.
[0053] According to an embodiment of the present invention, the smelting process includes the following steps: a. arc melting the alloy ingredients to obtain the master alloy ingot; b. induction melting the master alloy ingot, followed by cooling and solidification to obtain the cast metallic glass. Thus, the uniformity of the alloy composition is ensured, providing a homogeneous basic material for the subsequent glass-glass transition, thereby ensuring the consistency and reliability of the ultra-stable metallic glass.
[0054] According to an embodiment of the present invention, the heat treatment further comprises: heating the cast metallic glass to a temperature at which a glass-glass transition occurs and crystallization does not occur, and cooling the cast metallic glass to obtain an ultra-stable metallic glass. Thus, an ultra-stable metallic glass is prepared. Exemplarily, in the method 1 for preparing an ultra-stable metallic glass in an embodiment of the present invention, after heating the cast metallic glass to a temperature at which a glass-glass transition occurs and crystallization does not occur (the final temperature of the heat treatment) at a heating rate of 10K / min, cooling the cast metallic glass immediately to obtain an ultra-stable metallic glass. Thus, an ultra-stable metallic glass is prepared.
[0055] According to an embodiment of the present invention, the heat treatment further comprises: heating the cast metallic glass to a preset temperature at which a glass-glass transition occurs and crystallization does not occur and performing a heat preservation treatment, and performing a cooling treatment after the heat preservation treatment to obtain a superstable metallic glass; wherein the preset temperature is lower than the final temperature of the heat treatment. Exemplarily, in the preparation method 2 of the superstable metallic glass in the embodiment of the present invention, after heating the cast metallic glass to a preset temperature at which a glass-glass transition occurs and crystallization does not occur (the temperature is 5-10K lower than the final temperature of the heat treatment) at a heating rate of 10K / min, the cast metallic glass is kept at the preset temperature for about 20 minutes, and then cooled, and superstable metallic glass can also be prepared.
[0056] Therefore, according to the above two methods, ultra-stable metallic glass with no size restriction, high aging resistance, high anti-crystallization ability, better mechanical properties and durability can be produced.
[0057] It should be noted that the "not limited by size" mentioned in this article means that the size of the ultrastable metallic glass prepared by the preparation method of the present invention is completely determined by the size of the cast metallic glass. The size of the ultrastable metallic glass can be as large as the size of the cast metallic glass. The "not limited by size" is mainly for the ultrastable metallic glass prepared by the preparation method of the present invention has no size limitation within the range of glass forming ability, compared with the PVD method which can only prepare thin film ultrastable glass.
[0058] Ultrastable metallic glass
[0059] The present invention provides an ultra-stable metallic glass. According to an embodiment of the present invention, the ultra-stable metallic glass is prepared according to the aforementioned method. The ultra-stable metallic glass of the present invention has no size restriction, high aging resistance, high anti-crystallization ability, better mechanical properties and durability, and is suitable for different application scenarios.
[0060] According to an embodiment of the present invention, the alloy composition of the ultrastable metallic glass is expressed as Ti in atomic percentage. a Zr b Cu c Ni d Be e , where: 19%≤a≤21%, 19%≤b≤21%, 19%≤c≤21%, 19%≤d≤21%, 16%≤e≤24%, a+b+c+d+e=100%. Therefore, the ultra-stable metallic glass within the above alloy composition range has the advantages of no size restriction, high aging resistance, high crystallization resistance, better mechanical properties and durability. Exemplarily, according to an embodiment of the present invention, the ultra-stable metallic glass prepared includes Ti, zirconium, copper, nickel and beryllium as alloy ingredients. 20 Zr 20 Cu 20 Ni 20 Be 20 、Ti 21 Zr 21 Cu 21 Ni 21 Be 16 、Ti 19 Zr 19 Cu 19 Ni 19 Be 24 .
[0061] According to an embodiment of the present invention, the alloy composition of the ultrastable metallic glass is expressed as Ti in atomic percentage. A Hf B Cu C Ni D Be E , wherein: 19%≤A≤21%, 19%≤B≤21%, 19%≤C≤21%, 19%≤D≤21%, 16%≤E≤24%, A+B+C+D+E=100%. Thus, the ultra-stable metallic glass within the above alloy composition range has the advantages of no size restriction, high aging resistance, high crystallization resistance, better mechanical properties and durability. Exemplarily, according to an embodiment of the present invention, the ultra-stable metallic glass prepared includes Ti, hafnium, copper, nickel and beryllium as alloy ingredients. 20 Hf 20 Cu 20 Ni20 Be 20 .
[0062] According to an embodiment of the present invention, the alloy composition of the ultrastable metallic glass is expressed as Ti in atomic percentage. I Zr II Hf III Cu IV Ni V Be VI , where: I=II=III, 12%≤I≤14%, IV=V=VI, 19%≤IV≤22%, I+II+III+IV+V+VI=100%. Therefore, the ultra-stable metallic glass within the above alloy composition range has the advantages of no size restriction, high aging resistance, high crystallization resistance, better mechanical properties and durability. Exemplarily, according to an embodiment of the present invention, the ultra-stable metallic glass prepared includes (TiZrHf) when titanium, zirconium, hafnium, copper, nickel and beryllium are alloy ingredients. 40 Cu 20 Ni 20 Be 20 .
[0063] The scheme of the present invention will be explained below in conjunction with the embodiments. It will be appreciated by those skilled in the art that the following embodiments are only used to illustrate the present invention and should not be considered as limiting the scope of the present invention. Where specific techniques or conditions are not indicated in the embodiments, the techniques or conditions described in the literature in this area or the product specifications are used. The reagents or instruments used are not indicated by the manufacturer and are all conventional products that can be obtained commercially.
[0064] Example 1: The chemical composition expression is Ti 20 Zr 20 Cu 20 Ni 20 Be 20 Preparation of ultrastable metallic glass
[0065] The inventors used the glass-glass transition phenomenon in metallic glass and transformed ordinary metallic glass into an ultra-stable metallic glass with better anti-aging and anti-crystallization capabilities through heating and annealing. The chemical composition expression is Ti 20 Zr 20 Cu 20 Ni 20 Be 20 The preparation method of the ultrastable metallic glass (ultrastable metallic glass I) is as follows:
[0066] 1. Configuration of alloy ingredients
[0067] Titanium blocks, zirconium blocks, copper blocks, nickel blocks and beryllium blocks with a purity higher than 99.9wt% were selected for alloy preparation, and were weighed using a high-precision electronic balance with an accuracy of 0.0001g according to the atomic percentage of Ti:Zr:Cu:Ni:Be=1:1:1:1:1.
[0068] 2. Melting alloy ingredients
[0069] In vacuum environment, the vacuum degree is better than 3×10 -3 Pa, high-purity argon gas with a volume fraction of ≥99.999% is introduced to prevent the alloy ingredients from being oxidized or reacting unnecessary with other gases; under argon protection conditions, the above alloy ingredients are arc-melted for 1 min, and the arc melting operation is repeated 4 times to ensure the uniformity of the alloy ingot and obtain a master alloy ingot with uniform composition.
[0070] 3. Preparation of cast metallic glass I
[0071] Under the vacuum and high-purity argon conditions described in step 2, the master alloy ingot is melted by induction melting and sprayed onto the surface of a high-speed rotating copper roller to allow it to cool rapidly, wherein the copper roller speed is 3800 rpm (about 40 m / s), the spray pressure is 55.4 kPa, the bottom opening diameter of the quartz tube is 0.4 mm, and the current is about 19 A to obtain a metallic glass strip, i.e., cast metallic glass I.
[0072] 4. Determination of heating conditions
[0073] Take 20 mg of the above-mentioned metallic glass strip, use a differential scanning calorimeter (DSC) to heat the metallic glass strip at a heating rate of 10K / min until it is completely crystallized, and based on the obtained differential scanning calorimetry curve (DSC curve), determine the exothermic peak corresponding to the glass-glass transition when the atomic percentage of the alloy ingredients is Ti:Zr:Cu:Ni:Be=1:1:1:1:1 and the temperature range in which it occurs, including the starting temperature and the ending temperature (or final temperature), and determine the heat treatment conditions in this case accordingly.
[0074] The differential scanning calorimetry curve of cast metallic glass I shows Figure 1 .
[0075] The results show that at a heating rate of 10 K / min, the glass-glass transition end temperature of cast metallic glass I is 781 K.
[0076] The above results indicate that when the atomic percentage of the alloy ingredients is Ti:Zr:Cu:Ni:Be=1:1:1:1:1, the heating condition is heating to 781K at a heating rate of 10K / min.
[0077] 5. Preparation of ultrastable metallic glass
[0078] (1) Preparation method of ultrastable metallic glass 1
[0079] According to the temperature conditions obtained in step 4, another 50 mg of the above-mentioned metallic glass strips were taken and heated to 781 K at a heating rate of 10 K / min using a differential scanning calorimeter (DSC), and then cooled to room temperature at a cooling rate of 50 K / min to obtain ultrastable metallic glass I.
[0080] (2) Preparation method of ultrastable metallic glass
[0081] According to the temperature conditions obtained in step 4, take another several metallic glass strips mentioned above, place them in a quartz tube protected by Ar gas, and then place them together with the quartz tube in a heat treatment annealing furnace, heat them to 771K at a heating rate of 10K / min, and keep them at 771K for 20min, then take out the quartz tube and air-cool or water-cool it to room temperature, so as to obtain the ultra-stable metallic glass I.
[0082] The differential scanning calorimetry curves of cast metallic glass I and ultrastable metallic glass I are shown in Figure 1 .
[0083] Example 2: Chemical composition expression is Ti 21 Zr 21 Cu 21 Ni 21 Be 16 Preparation of ultrastable metallic glass
[0084] The chemical composition expression is Ti 21 Zr 21 Cu 21 Ni 21 Be 16 The preparation method of the ultrastable metallic glass (ultrastable metallic glass II) is as follows: the chemical composition expression in reference embodiment 1 is Ti 20 Zr 20 Cu 20 Ni 20 Be 20 The preparation method of the ultrastable metallic glass (ultrastable metallic glass I) is different from that of Example 1 in that the alloy ingredients are configured in step 1, and the other steps remain the same. The specific differences are as follows:
[0085] Titanium blocks, zirconium blocks, copper blocks, nickel blocks and beryllium blocks with a purity higher than 99.9wt% were selected for alloy preparation, and were weighed using a high-precision electronic balance with an accuracy of 0.0001g according to the atomic percentage of Ti:Zr:Cu:Ni:Be=21:21:21:21:16.
[0086] The differential scanning calorimetry curve of cast metallic glass II shows Figure 2 .
[0087] (1) Preparation method of ultrastable metallic glass 1
[0088] According to the temperature conditions obtained by the method in step 4 of reference example 1, several more metallic glass strips are taken, heated to 769 K at a heating rate of 10 K / min using a differential scanning calorimeter (DSC), and cooled to room temperature at a cooling rate of 50 K / min to obtain ultrastable metallic glass II.
[0089] (2) Preparation method of ultrastable metallic glass
[0090] According to the temperature conditions obtained by the method in step 4 of reference example 1, take another several metallic glass strips as mentioned above, place them in a quartz tube protected by Ar gas, and then place them together with the quartz tube in a heat treatment annealing furnace, and heat them to 759K at a heating rate of 10K / min, and keep them at 759K for 20 minutes, then take out the quartz tube and air-cool or water-cool it to room temperature, so as to obtain ultrastable metallic glass II.
[0091] The differential scanning calorimetry curves of cast metallic glass II and ultrastable metallic glass II are shown in Figure 2 .
[0092] Example 3: Chemical composition expression is Ti 19 Zr 19 Cu 19 Ni 19 Be 24 Preparation of ultrastable metallic glass
[0093] The chemical composition expression is Ti 19 Zr 19 Cu 19 Ni 19 Be 24 The preparation method of the ultrastable metallic glass (ultrastable metallic glass III) is as follows: the chemical composition expression in reference embodiment 1 is Ti 20 Zr 20 Cu 20 Ni 20 Be 20 The preparation method of the ultrastable metallic glass (ultrastable metallic glass I) is different from that of Example 1 in that the alloy ingredients are configured in step 1, and the other steps remain the same. The specific differences are as follows:
[0094] Titanium blocks, zirconium blocks, copper blocks, nickel blocks and beryllium blocks with a purity higher than 99.9wt% were selected for alloy formulation, and were weighed using a high-precision electronic balance with an accuracy of 0.0001g according to the atomic percentage of Ti:Zr:Cu:Ni:Be=19:19:19:19:24.
[0095] The differential scanning calorimetry curve of cast metallic glass III shows Figure 3 .
[0096] (1) Preparation method of ultrastable metallic glass 1
[0097] According to the temperature conditions obtained by the method of step 4 of reference example 1, several more of the above-mentioned metallic glass strips are taken, heated to 825K at a heating rate of 10K / min using a differential scanning calorimeter (DSC), and cooled to room temperature at a cooling rate of 50K / min to obtain ultrastable metallic glass III.
[0098] (2) Preparation method of ultrastable metallic glass
[0099] According to the temperature conditions obtained by the method in step 4 of reference example 1, take another several metallic glass strips as mentioned above, place them in a quartz tube protected by Ar gas, and then place them together with the quartz tube in a heat treatment annealing furnace, and heat them to 820K at a heating rate of 10K / min, and keep them at 820K for 20 minutes, then take out the quartz tube and air-cool or water-cool it to room temperature, so as to obtain ultra-stable metallic glass III.
[0100] The differential scanning calorimetry curves of cast metallic glass III and ultrastable metallic glass III are shown in Figure 3 .
[0101] Example 4: Chemical composition expression is Ti 20 Hf 20 Cu 20 Ni 20 Be 20 Preparation of ultrastable metallic glass
[0102] The chemical composition expression is Ti 20 Hf 20 Cu 20 Ni 20 Be 20 Preparation method of ultrastable metallic glass (ultrastable metallic glass IV), referring to Example 1 in which the chemical composition expression is Ti 20 Zr 20 Cu 20 Ni 20 Be 20The preparation method of the ultrastable metallic glass (ultrastable metallic glass I) is different from that of Example 1 in that the alloy ingredients are configured in step 1, and the other steps remain the same. The specific differences are as follows:
[0103] Titanium blocks, hafnium blocks, copper blocks, nickel blocks and beryllium blocks with a purity higher than 99.9wt% were selected for alloy formulation, and were weighed using a high-precision electronic balance with an accuracy of 0.0001g according to the atomic percentage of Ti:Hf:Cu:Ni:Be=19:19:19:19:24.
[0104] The differential scanning calorimetry curve of cast metallic glass IV shows Figure 4 .
[0105] (1) Preparation method of ultrastable metallic glass 1
[0106] According to the temperature conditions obtained by the method in step 4 of reference example 1, several more metallic glass strips are taken, heated to 823 K at a heating rate of 10 K / min using a differential scanning calorimeter (DSC), and cooled to room temperature at a cooling rate of 50 K / min to obtain ultrastable metallic glass IV.
[0107] (2) Preparation method of ultrastable metallic glass
[0108] According to the temperature conditions obtained by the method in step 4 of reference example 1, take another several metallic glass strips as mentioned above, place them in a quartz tube protected by Ar gas, and then place them together with the quartz tube in a heat treatment annealing furnace, and heat them to 813K at a heating rate of 10K / min, and keep them at 813K for 20 minutes, then take out the quartz tube and air-cool or water-cool it to room temperature, so as to obtain ultra-stable metallic glass IV.
[0109] The differential scanning calorimetry curves of cast metallic glass IV and ultrastable metallic glass IV are shown in Figure 4 .
[0110] Example 5: The chemical composition expression is (TiZrHf) 40 Cu 20 Ni 20 Be 20 Preparation of ultrastable metallic glass
[0111] The chemical composition expression is (TiZrHf) 40 Cu 20 Ni 20 Be 20 Preparation method of ultrastable metallic glass (ultrastable metallic glass V), referring to Example 1 in which the chemical composition expression is Ti 20 Zr 20 Cu 20 Ni20 Be 20 The method for preparing ultrastable metallic glass, compared with Example 1, is different in the configuration of alloy ingredients in step 1, and the other steps remain the same. The specific differences are as follows:
[0112] Titanium blocks, zirconium blocks, hafnium blocks, copper blocks, nickel blocks and beryllium blocks with a purity higher than 99.9wt% were selected for alloy preparation, and were weighed using a high-precision electronic balance with an accuracy of 0.0001g according to the atomic percentage of Ti:Zr:Hf:Cu:Ni:Be=13.3:13.3:13.3:20:20:20.
[0113] (1) Preparation method of ultrastable metallic glass 1
[0114] The differential scanning calorimetry curve of cast metallic glass V shows Figure 5 .
[0115] According to the temperature conditions obtained by the method in step 4 of reference example 1, several more of the above-mentioned metallic glass strips are taken, heated to 790K at a heating rate of 10K / min using a differential scanning calorimeter (DSC), and cooled to room temperature at a cooling rate of 50K / min to obtain ultra-stable metallic glass V.
[0116] (2) Preparation method of ultrastable metallic glass
[0117] According to the temperature conditions obtained by the method in step 4 of reference example 1, take another several metallic glass strips as mentioned above, place them in a quartz tube protected by Ar gas, and then place them together with the quartz tube in a heat treatment annealing furnace, and heat them to 780K at a heating rate of 10K / min, and keep them at 780K for 20min, then take out the quartz tube and air-cool or water-cool it to room temperature, so as to obtain the ultra-stable metallic glass V.
[0118] The differential scanning calorimetry curves of cast metallic glass V and ultrastable metallic glass V are shown in Figure 5 .
[0119] Example 6: Comparative test of the structure and performance of cast metallic glasses I to IV and ultrastable metallic glasses I to IV
[0120] The structural performance tests of the cast metallic glasses I to IV and the ultrastable metallic glasses I to IV prepared in Examples 1 to 5 were conducted in the following specific steps:
[0121] (1) X-ray diffraction
[0122] X-ray diffraction (XRD) was used to confirm whether the ultrastable metallic glass I and the cast metallic glass I were amorphous structures. The specific parameters were: Cu Kα radiation was used and the scanning rate was 2° / min.
[0123] The XRD results of cast metallic glass I and ultrastable metallic glass I are shown in Figure 6 .
[0124] The XRD results of cast metallic glass II and ultrastable metallic glass II are shown in Figure 7 .
[0125] The XRD results of cast metallic glass III and ultrastable metallic glass III are shown in Figure 8 .
[0126] The XRD results of cast metallic glass IV and ultrastable metallic glass IV are shown in Fig. 9 .
[0127] The XRD results of cast metallic glass V and ultrastable metallic glass V are shown in Fig.10 .
[0128] Combination Figures 1 to 10 The results show that the XRD spectra of cast metallic glasses I~V and ultrastable glasses I~V are typical "mantou peaks" without sharp Bragg diffraction peaks, indicating that they are all fully amorphous structures within the XRD detection accuracy.
[0129] (2) Transmission electron microscopy
[0130] Transmission electron microscopy (TEM) was used to detect cast metallic glass I and ultrastable metallic glass I. The presence of lattice fringes was confirmed based on the image results, thereby determining whether the sample had an amorphous structure.
[0131] The TEM results of cast metallic glass I and ultrastable metallic glass I are shown in Fig.11 .
[0132] The results show that the HRTEM images of cast metallic glass I and superstable glass I are both typical maze-like patterns, with no lattice fringes, indicating that both are completely amorphous structures at the nanoscale without nanocrystal precipitation. The SAED of both shows diffuse diffraction rings without sharp diffraction spots. No obvious contrast is seen in the HADDF of the two, indicating that the two glasses have uniform compositions and no phase separation or nanocrystallization occurs. In short, the TEM structure fully proves that the superstable glass obtained by heat treatment is a completely amorphous structure.
[0133] (3) Synchrotron Radiation
[0134] The data of the distribution function G(r) were obtained using synchrotron radiation, and the degree of structural order of ultrastable metallic glass I and cast metallic glass I was quantified by fitting the G(r) curve.
[0135] The distribution function G(r) of cast metallic glass I and ultrastable metallic glass I can be found in Fig.12 .
[0136] The results show that the distribution function curve G(r) shows the structural differences between the two glasses, especially the structures at the medium-range scale are significantly different. Intuitively, the G(r) curve of the superstable glass decays more slowly, indicating that its structure is more ordered. The peak height h(r) and r of the G(r) curve were fitted using an exponential decay function: h(r) = A·exp(-r / ξ), where A is the amplitude and ξ is the cutoff distance. ξ quantitatively measures the speed of the G(r) curve decay. The larger the ξ, the slower the decay, indicating that the order of the alloy structure has increased. Cutoff distance of superstable metallic glass As-cast The improvement was 62.3%, reflecting the obvious ordering of its structure.
[0137] (4) Thermodynamic performance test
[0138] Flash DSC results were obtained by heating and detecting at a heating rate of 1000 K / s using flash differential scanning calorimetry (flash DSC).
[0139] The flash DSC results of cast metallic glass I and ultrastable metallic glass I are shown in Fig.13 .
[0140] The results show that at an ultrafast heating rate of 1000K / s, the glass transition temperatures of cast and ultrastable metallic glasses are calibrated (typical curves are shown in Figure 2). Fig.13 The statistical results are shown in Table 1). The higher the glass transition temperature, the higher the energy required to excite atoms from the confined glass state to the mobile equilibrium supercooled liquid state. The glass transition temperature of the ultrastable metallic glass is 12.8% higher than that of the cast state, indicating that its dynamic stability is greatly improved compared with the cast metallic glass.
[0141] (5) Density test
[0142] Density tests were performed to compare the ultrastable metallic glass I and cast metallic glass I obtained by the preparation method of the present invention, the ultrastable metallic glass prepared by physical vapor deposition, and the ultrastable metallic glass obtained by natural aging.
[0143] The density of ultrastable metallic glass I and cast metallic glass I was tested by gas replacement method, wherein the test temperature was 35±0.01°C and the replacement gas used was helium with a purity of 99.999%. The density data of ultrastable metallic glass prepared by physical vapor deposition method and ultrastable metallic glass prepared by natural aging method were derived from existing literature.
[0144] The comparative density test results of ultrastable metallic glass I are shown in Fig.14 .
[0145] The results show that density is an important indicator reflecting the thermodynamic stability of glass. The lower the energy state of the glass, the higher its density, and the closer it is to the density of the corresponding crystalline state. Compared with cast metallic glass I, the density of ultrastable glass I increased by 2.3%; compared with the crystalline state, the density of ultrastable glass I was only 0.7% lower. The density increases caused by physical vapor deposition, natural aging and this method were compared. The density increase of ultrastable glass prepared by physical vapor deposition is generally 1-2% compared with cast metallic glass, while the density increases of 110 million-year-old amber and 17.7-year-old Ce-Al-Cu metallic glass are 2.05% and 1.19%, respectively. The density increase of ultrastable metallic glass I prepared by the present invention is 2.3%, which is higher than the previously reported value of ultrastable glass.
[0146] (6) Mechanical properties test
[0147] Nanoindentation method was used to test the hardness and reduced modulus of ultrastable metallic glasses I-V and cast metallic glasses I-V. The loading and unloading rates in the tests were both 1 mN s -1 , the maximum load is 30mN, and the holding time at the maximum load is 5s.
[0148] The density, modulus, hardness, glass transition temperature (Tg), supercooled liquid phase width (ΔT) of cast metallic glass I and ultrastable metallic glass I and the density, modulus and hardness of the corresponding crystalline state are shown in Table 1.
[0149] Table 1
[0150]
[0151] Among them, the crystalline state is the product of the complete crystallization of cast metallic glass I, T g@1000K / s is the glass transition temperature at 1000K / s, ΔT @10K / min is the width of the supercooled liquid phase measured at 10K / min
[0152] The results show that compared with cast metallic glass I, the modulus and hardness of ultra-stable glass I increased by 26.9% and 26.0%, respectively. As a structural sensitive quantity, the huge change in modulus indicates that the structure of the alloy has changed significantly. The modulus of general metallic glass is about 30% lower than that of the corresponding crystalline state, which is called the "modulus softening" effect; while the modulus of the ultra-stable glass in the results of the present invention is only 5.1% lower than that of the crystalline state, indicating that the energy state of the ultra-stable glass is close to that of the crystalline state.
[0153] The changes in modulus and hardness of ultrastable metallic glasses I~V relative to cast metallic glasses I~V are shown in Table 2.
[0154] Table 2
[0155] Modulus increase (%) Hardness increase (%) Ultrastable metallic glass I compared to cast metallic glass I 27.0 26.0 Ultrastable metallic glass II compared to cast metallic glass II 29.0 30.2 Ultrastable metallic glass III compared to cast metallic glass III 19.8 21.6 Ultrastable metallic glass IV compared to cast metallic glass IV 20.0 28.1 Ultrastable metallic glass V compared to cast metallic glass V 17.4 22.5
[0156] The results show that the modulus of ultrastable metallic glasses I to V increases by 17.4 to 29.0% and the hardness increases by 21.6 to 30.2% after the glass-glass transition. Such a significant increase in modulus and hardness cannot be achieved by simple relaxation annealing, which confirms that the glass obtained after annealing is an ultrastable metallic glass.
[0157] (7) Anti-crystallization ability test
[0158] Using differential scanning calorimetry (DSC), the ultrastable metallic glass I was characterized at its T g The alloy was kept at +70K for 10h, and the crystallization resistance and mechanical property stability of the prepared alloy were tested by differential scanning calorimetry, X-ray diffraction (XRD) and nanoindentation tests.
[0159] Ultrastable metallic glass I at its T g XRD patterns, DSC curves and nanoindentation load-displacement curves before and after annealing at +70K for 10h are shown in Fig.15 .
[0160] The results show that after 10 hours of high-temperature annealing, the XRD spectrum still maintains a diffuse "mantou peak" shape, and no sharp Bragg diffraction peak is seen, indicating that the ultrastable metallic glass I sample remains amorphous and does not crystallize; and from the comparison of the DSC curves before and after annealing, it can be seen that the crystallization enthalpy has not decreased, confirming the conclusion that no crystallization has occurred. The modulus and hardness of the ultrastable metallic glass I sample before and after annealing were tested by nanoindentation, and it was found that the modulus and hardness only increased by 0.9% and 3.5%, respectively, proving that the mechanical properties of the ultrastable metallic glass I sample remain quite stable.
[0161] Although the embodiments of the present invention have been shown and described above, it is to be understood that the above embodiments are exemplary and are not to be construed as limitations of the present invention. A person skilled in the art may change, modify, replace and vary the above embodiments within the scope of the present invention.
Claims
1. A method for preparing ultrastable metallic glass, characterized in that: include: S1: melting the alloy ingredients to obtain cast metallic glass; S2: heat-treating the cast metallic glass so that it undergoes a glass-glass transition without crystallization, thereby obtaining an ultra-stable metallic glass; The process parameters of the heat treatment are determined by the differential scanning calorimetry curve of the cast metallic glass, and the temperature at which the glass-glass transition occurs and no crystallization is determined by the exothermic peak in the differential scanning calorimetry curve is used as the final temperature of the heat treatment.
2. The method according to claim 1, characterized in that: The alloy ingredients include two or more of titanium, zirconium, hafnium, copper, nickel, beryllium, cobalt, aluminum, niobium, lanthanum, cerium and cobalt; Optionally, the alloy ingredients include titanium, zirconium, copper, nickel and beryllium; Optionally, the alloy ingredients include titanium, hafnium, copper, nickel and beryllium; Optionally, the alloy formulation includes titanium, zirconium, hafnium, copper, nickel and beryllium.
3. The method according to claim 1, characterized in that The smelting process comprises the following steps: a. arc melting the alloy ingredients to obtain a master alloy ingot; b. After the master alloy ingot is melted by induction melting, it is cooled and solidified to obtain the cast metallic glass.
4. The method according to claim 1, characterized in that: The heat treatment further comprises: The cast metallic glass is heated to a temperature at which a glass-glass transition occurs but crystallization does not occur, and then cooled to obtain an ultra-stable metallic glass.
5. The method according to claim 1, characterized in that: The heat treatment further comprises: The cast metallic glass is heated to a preset temperature at which a glass-glass transition occurs but crystallization does not occur and then subjected to a heat preservation treatment, and then subjected to a cooling treatment after the heat preservation treatment to obtain a superstable metallic glass; Wherein, the preset temperature is lower than the final temperature of the heat treatment.
6. An ultrastable metallic glass, characterized in that: The ultrastable metallic glass is prepared according to the method according to any one of claims 1 to 5.
7. The ultrastable metallic glass according to claim 6, characterized in that: The alloy composition of the ultrastable metallic glass is expressed as Ti in atomic percentage. a Zr b Cu c Ni d Be e , where: 19%≤a≤21%, 19%≤b≤21%, 19%≤c≤21%, 19%≤d≤21%, 16%≤e≤24%, a+b+c+d+e=100%; Optionally, the alloy composition of the ultrastable metallic glass is expressed as Ti in atomic percentage. A Hf B Cu C Ni D Be E , among which: 19%≤A≤21%, 19%≤B≤21%, 19%≤C≤21%, 19%≤D≤21%, 16%≤E≤24%, A+B+C+D+E=100%; Optionally, the alloy composition of the ultrastable metallic glass is expressed as Ti in atomic percentage. I Zr II Hf III Cu IV Ni V Be VI , where: I=II=III, 12%≤I≤14%, IV=V=VI, 19%≤IV≤22%, I+II+III+IV+V+VI=100%.
Citation Information
Patent Citations
Ti-based bulk metallic glass
CN102108475A
Preparation method of block amorphous alloy
CN106244999A
Zr-Al-Ni-Cu block metal glass with different crystallized phase categories, contents and performance
CN108504968A
Production of amorphous magnesium alloy
JP1994081054A
Zr / ti-based two phase metallic glasses
KR1020070108705A